Elastic Properties of Lanthanum Modified Lead Zirconate Titanate Ferroelectric Ceramics - Shabbir, G. (The Nucleus, 2014)
Elastic properties of lanthanum-modified lead zirconate-titanate (PLZT) relaxor ceramic oxide used as optical shutters are required for device design, storage and field purposes. Therefore, acoustic phonon mode velocity and related elastic constant of PLZT ceramic were measured by the non-destructive high-resolution Brillouin light scattering technique in the temperature range from 700 K down to 200 K. Broad anomalies were observed in the acoustic phonon velocity and the elastic constant showing minimum between 320 – 240 K showing a typical relaxor ferroelectric character. A broad central peak was also observed at 200≤T≤500 K. The temperature dependence of the acoustic anomaly and central peak was associated to the fluctuations of the local polarization caused by the polar nanoregions.